Traditional Chinese Medicine Pien-Tze-Huang Inhibits Colorectal Cancer Growth and Immune Evasion by Reducing β-catenin Transcriptional Activity and PD-L1 Expression - Chen, Qiang; Hong, Yilin; Weng, Shihe; Guo, Peng; Li, Bei; Zhang, Yong; Yu, Chundong; Wang, Shicong; Mo, Pingli (Frontiers in Pharmacology, 2022)
Pien Tze Huang (PZH) is a valuable traditional Chinese medicine, which has a variety of biological activities such as clearing heat-toxin, resolving blood stasis, detoxifying, relieving pain, and anti-inflammation. PZH has a partial role in suppressing the progression of CRC, while the underlying mechanism is a pending mystery; especially whether PZH mediates the immune escape of CRC remains unclear. Our study reported that PZH suppressed the proliferative activity of CRC by inhibiting Wnt/β-catenin signaling to down-regulate the expression of PCNA and Cyclin D1. In addition, PZH suppressed the immune escape of CRC and elevated the infiltration of CD8+ T cells in tumor tissues, which depends on the suppression of PD-L1 levels via inhibiting IFNGR1-JAK1-STAT3-IRF1 signaling. More importantly, PZH pharmacologically elevated the antitumor efficacy of anti-PD-1/PD-L1 immunotherapy as demonstrated by slower tumor growth, higher infiltration and function of CD8+ T cells in the combination of PZH and PD-1/PD-L1 antibody compared with monotherapy with either agent. These results demonstrate that PZH has the potential role in inhibiting CRC proliferation and immune evasion, especially the synergistic enhancement effect of PZH on immunotherapy.